2009
DOI: 10.1089/lap.2009.0122
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Technique for the Surgical Treatment of Achalasia in Children: Evaluated with Postoperative Esophageal Manometry

Abstract: The proposed surgical technique for the treatment of achalasia in children was successful at improving feeding and weight gain and attaining normal postoperative LES tone; however, underlying esophageal dysmotility persisted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…also found distal esophageal peirstalsis after endoscopic dilation in several patients. Loqan et al . reported that after Heller's surgery, 4/7 subjects showed partial esophageal peristalsis and less synchronized contractions, and they thought this change was insignificant and could not conclude that surgery would help to restore peristalsis.…”
Section: Discussionmentioning
confidence: 99%
“…also found distal esophageal peirstalsis after endoscopic dilation in several patients. Loqan et al . reported that after Heller's surgery, 4/7 subjects showed partial esophageal peristalsis and less synchronized contractions, and they thought this change was insignificant and could not conclude that surgery would help to restore peristalsis.…”
Section: Discussionmentioning
confidence: 99%